2006
DOI: 10.1007/s10600-006-0253-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial activity of the essential oils of Ferula latisecta and Mozaffariania insignis from Iran

Abstract: The hydrodistilled oils from the aerial parts of Ferula latisecta and Mozaffariania insignis, which is endemic to Iran, were analyzed by GC and GC/MS. (Z)-Ocimenone (32.4%), (E)-ocimenone (20.3%), and cis-pinocarvone (11.4%) were the main components among the 22 constituents characterized in the oil of F. latisecta, representing 87.7% of the total components detected. Twenty-five compounds were identified in the oil of M. insignis, representing 99.0% of the total oil, with octyl acetate (41.1%), β-pinene (30.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…The former species, which forms a separate subgroup, i.e., OS-1, belongs to the monotypic subgenus Scorodosma, whereas the two latter species, forming the subgroup OS-2, were attributed to the subgenus Merwia. While the leave essential oils of F. latisecta characterized by Iranshahi et al [17] exhibited similarity to the present oil, the oil extracted from the aerial parts of this species by Habibi et al [18] showed a different general oil profile. In the essential oil of F. assa-foetida reported by Khajeh et al [29] and our present oil, 1-methylpropyl (1E)-prop-1-en-1-yl disulfide (3) was detected as the main constituent.…”
mentioning
confidence: 45%
“…The former species, which forms a separate subgroup, i.e., OS-1, belongs to the monotypic subgenus Scorodosma, whereas the two latter species, forming the subgroup OS-2, were attributed to the subgenus Merwia. While the leave essential oils of F. latisecta characterized by Iranshahi et al [17] exhibited similarity to the present oil, the oil extracted from the aerial parts of this species by Habibi et al [18] showed a different general oil profile. In the essential oil of F. assa-foetida reported by Khajeh et al [29] and our present oil, 1-methylpropyl (1E)-prop-1-en-1-yl disulfide (3) was detected as the main constituent.…”
mentioning
confidence: 45%
“…The main component identified in the essential oils of F. flabolliloba 43 , F. latisecta 49 , F. persica 60 , from Iran, was δ-cadinene (13.2 %), (Z)-ocimenone (32.4 %) and dillapiole (57.3 %), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we reported the oils composition of some species of this genus found in Iran [43][44][45][46][47][48][49][50] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the strong antimicrobial effects of Z. absinthifolia fruit oil could be primarily due to the presence of 1-octanol in the oil. On the other hand, essential oils with high amount of octyl acetate exhibit antibacterial effects (Habibi et al, 2006). Hence, it is possible that octyl acetate might be involved in some type of synergism with 1-octanol in causing the antimicrobial effects of the essential oil of Z. absinthifolia fruits.…”
Section: Natural Product Research 1127mentioning
confidence: 99%